A new high-throughput screening-compatible gap junctional intercellular communication assay. Issue 1 (December 2015) - Lee, Ju; Choi, Eun; Lee, Jinu
Abstract Background Gap junctions (GJs) are intercellular channels through which molecules smaller than 1 kDa can diffuse, and they have been suggested as drug targets. To develop chemical drugs acting on this target, a high-throughput screening (HTS) system for GJ modulators is necessary. Results We designed a new, high-throughput GJ intercellular communication (GJIC) assay. This assay system consisted of donor and acceptor cells from LN215 glioma cells that expressed SLC26A4 and yellow fluorescent protein-H148Q/I152L (YFPQL ), respectively. The fluorescence of LN215-YFPQL acceptor cells, when cultured alone, was not quenched by iodide. However when donor and acceptor cells, or LN215-YFPQL and LN215-I− cells, were mixed and plated, they formed GJs. When iodide was added, it was transported into donor cells by SLC26A4, diffused through the GJs to acceptor cells, and quenched the YFPQL fluorescence. The quenching rate was optimal at a 2:1 mixture of donor and acceptor cells. The assay quality parameter, Z' factor, was calculated from data collected with vehicle and carbenoxolone. For each assay, the Z' factor increased with time. The Z' factor of a 10-s assay was 0.72 indicating that the assay quality was high enough for use in HTS. This assay system also worked well in HOS osteosarcoma cells with a Z' factor at 10 s of 0.70. Conclusions We developed a new HTS system for GJ modulators. The system had a high assay quality with a Z' factor ≥ 0.70, was rapid and required only 10 s per well, was inexpensive in requiring no additional reagents, and was predicted to have a low rate of false-positive hits.